Taxonomy of 'Euconnus complex'. Part III. Morphology of Euconnus subgenus Napochus and revision of the Australian species (Coleoptera, Staphylinidae, Scydmaeninae) - Jałoszyński, Paweł (Zootaxa, 2015)
Morphological structures of the type species of Euconnus (Napochus) are described and illustrated, and compared with those of Euconnus s. str. Napochus is maintained as a subgenus of Euconnus, and its revised diagnosis is given. Australian species of Napochus are revised: E. palmwoodianus Franz and E. pisoniae Franz are redescribed, and E. setiphallus sp. n., E. yadhaigana sp. n., E. microlaminatus sp. n, E. feeneyi sp. n. (with a subspecies E. feeneyi parallelilaminatus ssp. n.) are described. An unusual variability in body size and proportions of body parts found in E. feeneyi is analyzed and discussed.